PENGARUH PEMBENTUKAN CITRA PDAM TERHADAP OPINI MASYARAKAT TULUNGAGUNG - Rosiana Andhikasari; Arina Muntazah (Yayasan Akrab Pekanbaru, 2019)
This study is aimed to investigate the effect of image formation factor components such as physical identity, non physical identity, organitation management, product quality, activity and relations. Besides, it is also used to know which component has the biggest part in influencing the public opinion. Variable X1 is physical identity, variable X2 is non physical identity, variable X3 is organitation management, Variable X4 is product quality, Variable X5 is activity and relations, and variable Y is public opinion. Related literature used in this research is image formation and public opinion. This research belongs to quantitative research with corelational description. Sample employed here is 100 people. In gathering the data, questionnaire is used and the result is counted by using likert scale. Moreover, to make the data valid, some tests are also used. They are validity test, reliability test, and classic assumption test that covers normality test and multicollinearity test. Furthermore, the data are analyzed by using double linier regression analysis. From the results of data analysis and discussion it was found that together the variables of physical identity (X1), non physical identity (X2), organitation management (X3), product quality (X4), activity and relations (X5) have a significant effect on public opinion (Y). The contribution of these five variables amounted to 59.1%, the remaining approximately 40.9% influenced by other factors besides these five variables. The existence of influence together, indicating that these five variables is what determines the level of public opinion.